Proteomics in Foods Principles and Applications - Toldrá, Fidel Nollet, Leo M. L. (Food Microbiology and Food Safety Series, v. 2., 2013)
This book provides readers with the recent advances and state-of-the-art in food proteomics, which constitutes one of the most relevant and rapidly developing areas in food science. The first part covers the principles of proteomics, including an in-depth discussion of the proteome, as well as the extraction and fractionation techniques for proteins and peptides, separation techniques like 2-D electrophoresis and chromatography, and mass spectrometry applications. The second part covers applications to foods, such as quality issues related with post-mortem processes in animal foods, and quality traits for a wide variety of foods like meat, fish, dairy, eggs, wine, beer, cereals, fruits and vegetables. Also discussed are the identification of bioactive peptides and proteins, crucial from a nutritional perspective, and safety issues like food authenticity, detection of animal species in the food, markers of pathogen microorganisms, and identification of prions.